Isolation and characterization of oil degrading bacteria from a local ecological sanitation (ECOSAN) system - Delima, anak Andrew Buntak. (Universiti Malaysia Sarawak (UNIMAS), 2008)
Eight bacterial isolates (B I, B2, B3, B4, B5, B6, B7 and B8) were isolated from the oil and grease trap of a Grey Water Treatment System (ECOSAN System) in Kenanga College. Four of the bacterial isolates were identified based on API 20E system as follows: B2 -Chromobacterium violeceum, B4 -Pseudomonas aeruginosa, B7 ,-Pseudomonas fluorescent/pulida and B8 -Klebsiella pneumonia pneumonia while three of them were identified based on 16S rRNA sequencing as follows: B3 -Bacillus sp. CNJ782 PL04, B5 -Pseudomonas aeruginosa Strain PDIOO and B6 -Pseudomonas aeruginosa strain RII. However, B 1 was unidentifiable. All the eight isolates were positively screened as oil degrading bacteria by using Rhodamine B agar. B4 can be concluded as having the highest degradation activity when incubated with both 1 % and 2% Tween 20 and Tween 80 compared to the other bacterial isolates.